PERGESERAN PERAN AKUNTANSI MANAJEMEN PADA ERA GLOBALISASI - AYU KRISNADEWI, KOMANG (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010))
Business environment changes would affect mindset of corporate management. In the previous, accounting was used by management to control subordinates. Performance evaluation emphasized more in financial aspect. Today, in the globalization era, corporate would give their best efforts to win business competition related to economic environment, and not dictated by accounting numbers. Management shall not pay attention only on accounting-based control – financial aspect, because accounting has developed to embrace non financial aspect as well.
Keywords: business environment, globalization, management accounting, financial, non financial aspect